Preparation of Multiferroic YFeO3 Nanofibers and the Photocatalytic Activity under Visible Irradiation. Issue 206 (23rd March 2020) - Zhang, Runlan; Wang, Xiaoqin; Yu, Chunxia; Liu, Jian; Yao, Junjie; Kang, Xiaoying; Xing, Xingxing; Xiong, Shanxin
Abstract: Multiferroic YFeO3 nanofibers were prepared by electrospinning. The as-prepared nanofibers were characterized by XRD, TG-DTA, SEM and Raman spectrum. The magnetic property and photocatalytic activity of the orthorhombic YFeO3 nanofibers were also investigated. The results show that the crystal structure and morphology of the YFeO3 nanofibers were influenced by the calcination temperature. Pure orthorhomic YFeO3 nanofibers can be obtained when the temperature increased to 860 °C and they exhibit ferromagnetism with slight antiferromagnetism at room temperature. The degradation test of RhB and MB under simulated sunlight show that the YFeO3 nanofibers possess higher photocatalytic activity, compared with the YFeO3 nanoparticles.